Green Economy Innovation in Attracting Youth to Pond Fish Farming Profession : Inovasi Ekonomi Hijau dalam Menarik Minat Pemuda pada Profesi Budidaya Ikan Tambak - Zulkarnaen, Have; Arisandra, Martha Laila (Indonesian Journal of Innovation Studies, 2024)
The purpose of this study was to determine and analyze the effect of youth perceptions on interest in the fish farming profession mediated by green economy. The approach used in this research is a causal approach. The population in this study were village youth in Sungelebak, Sungegeneng Kec, Lamongan Kab. The sample in this study used simple random sampling with 100 respondents. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Test. Data processing in this study used the PLS (Partial Least Square) software program. The results of this study prove that directly youth perceptions and green economy have a significant effect on interest in the fish farming profession and indirectly green economy is able to mediate the effect of youth perceptions on interest in the fish farming profession. Highlights: Significant Relationships: Youth perceptions and green economy significantly influence interest in fish farming. Mediation Effect: Green economy acts as a mediator between youth perceptions and fish farming interest. Methodology: Utilized a causal approach with 100 respondents from Sungelebak village through questionnaires and PLS software. Keywords: Youth Perception, Green Economic, Interest in Fish Farming Profession